Piezoelectric and Ferroelectric Properties of (Bi0.5Na0.5)0.9Ba0.07Sr0.03TiO3 Lead-Free Ceramics with MnO2 Doping - Yin, Qiyi; Ding, Ming; Tian, Changan; Lu, Hongdian; Cheng, Jihai; Zhou, Yingying (Asian Journal of Chemistry, 2012)
The effect of a small amount MnO2 doping on the piezoelectric and ferroelectric properties of (Bi0.5Na0.5)0.9Ba0.07Sr0.03TiO3 (BNBST) lead-free ceramics prepared by the conventional mixed oxide method was systematically investigated. At x = 0.25, the MnO2-modified BNBST ceramics exhibit optimal piezoelectric and dielectric properties (d33 = 157pC/N, kp = 33 %, Qm = 364, tan d = 2 %, er = 843) and excellent ferroelectric properties composed by a higher remanent polarization Pr (Pr = 25.9 μC/cm2) and lower coercive field EC (EC = 2.54 kV/mm) at room temperature. Moreover, the two characteristic dielectric peaks can be observed in this ceramics.